1999
DOI: 10.1097/00002030-199910010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Positive and sustained effects of highly active antiretroviral therapy on HIV-1-associated neurocognitive impairment

Abstract: HAART produces a positive and sustained effect on neurocognitive impairment in HIV-infected patients. A reduction of plasma viral load was associated with the regression of neuropsychological test abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
2
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(87 citation statements)
references
References 15 publications
6
77
2
2
Order By: Relevance
“…8 Subsequently, several observational studies independently reported significant NP improvements in patients receiving protease inhibitor (PI)-based HAART (Table 1). 27,28 Additional studies confirmed the finding in different populations including women 29,30 and patients in sub-Saharan Africa (Table 1). 31 Moreover, it was shown that the cognitive domains enhanced with HAART were psychomotor speed, verbal anterograde memory, and executive functions, thus supporting the idea that HAART could revert cognitive dysfunction by improving subcortical cognitive functions.…”
Section: Haart Improves Neurocognitive Functionsupporting
confidence: 76%
See 1 more Smart Citation
“…8 Subsequently, several observational studies independently reported significant NP improvements in patients receiving protease inhibitor (PI)-based HAART (Table 1). 27,28 Additional studies confirmed the finding in different populations including women 29,30 and patients in sub-Saharan Africa (Table 1). 31 Moreover, it was shown that the cognitive domains enhanced with HAART were psychomotor speed, verbal anterograde memory, and executive functions, thus supporting the idea that HAART could revert cognitive dysfunction by improving subcortical cognitive functions.…”
Section: Haart Improves Neurocognitive Functionsupporting
confidence: 76%
“…51 Most cohort studies also indicate that use of HAART is associated with improved cognition. 3,6,[26][27][28][29][30][31][32][33][34][35]37,38,[40][41][42]45,46,48,49,55,56 Interestingly, almost all randomized studies 8,24,25,36,50,51 and carefully designed prospective cohorts on advanced and/or cognitively impaired patients 30 in cognition with HAART use. Improvements were more pronounced in severely cognitively impaired subjects 48 and occur within a few weeks of ARV therapy initiation or change.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely believed HAD cognitive impairments are associated with the number of immune competent and HIV-1-infected MP (Glass et al 1995), diminished synaptic and dendritic density Everall et al 1999), and selective neuronal loss (Masliah et al 1992;Fox et al 1997). However, not all HAD patients exhibit profound neuronal loss (Seilhean et al 1993) and improvements in cognitive function have been observed after HAART (Ferrando et al 1998;Gendelman et al 1998;Tozzi et al 1999;Robertson et al 2004). This suggests that cognitive decline may result as much from neuronal dysfunction as from neuronal loss, an idea supported by experimental results showing alterations in cell layer volume and dendritic morphology ) correlate with HAD (Gray et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy has dramatically reduced the incidence and severity of opportunistic infections associated with HIV and improved neurocognitive function [1,2], but it remains unclear how effectively antiretroviral therapy protects the CNS against HIV-related disease. Many investigators have used event-related brain potentials (ERPs) to assess CNS function in HIV patients; however, most of have focused on phasic components such as the P300.…”
Section: Introductionmentioning
confidence: 99%